Failing Grade: 89% of Introduction-to-Psychology Textbooks That Define or Explain Statistical Significance Do So Incorrectly. Issue 3 (September 2019) - Cassidy, Scott A.; Dimova, Ralitza; Giguère, Benjamin; Spence, Jeffrey R.; Stanley, David J.
Null-hypothesis significance testing (NHST) is commonly used in psychology; however, it is widely acknowledged that NHST is not well understood by either psychology professors or psychology students. In the current study, we investigated whether introduction-to-psychology textbooks accurately define and explain statistical significance. We examined 30 introductory-psychology textbooks, including the best-selling books from the United States and Canada, and found that 89% incorrectly defined or explained statistical significance. Incorrect definitions and explanations were most often consistent with the odds-against-chance fallacy. These results suggest that it is common for introduction-to-psychology students to be taught incorrect interpretations of statistical significance. We hope that our results will create awareness among authors of introductory-psychology books and provide the impetus for corrective action. To help with classroom instruction, we provide slides that correctly describe NHST and may be useful for introductory-psychology instructors.